PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE TEAMS GAMES TOURNAMENT TERHADAP KETERAMPILAN MENULIS SURAT LAMARAN PEKERJAAN - Hasmi, Lili; W, Yuhelmi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
This study aims to describe the effect of using the cooperative teams games tournament learning model on the skills of writing job application letters for class XII students of SMA Negeri . This type of research is quantitative research using experimental methods. In this study, two classes were used, namely the experimental class and the kontrol class. Total population of 185 students, sampling using purposive sampling sampling, with a total sample of 50 students spread from the experimental class 25 students and the control class amounted to 25 students. This research instrument uses a performance test with assessment indicators, the first is the systematic aspect of the job application letter and the second is the linguistic aspect of the job application letter. Based on the results of data analysis, it can be concluded that the results of the t-test (t-test) in the experimental class prove tcount with ttable (4,201>2,064), because tcount is greater than ttable then H1 (alternative hypothesis) is accepted. Furthermore, the results of the t-test (t-test) in the control class prove tcount with ttable (2,270>2,064), because tcount is greater than t〗 _table then H1 (alternative hypothesis) is accepted. The results of the t-test (t-test) are the results of the comparison of tcount with ttable (2,706>2,021), because tcount is greater than ttable, then H1 (alternative hypothesis) is accepted. So, the skill of writing a job application letter has a strong effect using the cooperative teams games tournament learning model compared to the skill of writing a job application letter using the conventional method. Keywords: Writing, Job Application Letter, Teams Games Tournament Model